Intermittent fasting before laparotomy: Effects on glucose control and histopathologic findings in diabetic rats - Hsu, André Keng Wei [UNESP]; Roman, Silvane Souza; Bagatini, Margarete Dulce; Marafon, Filomena; Junior, Paulo Do Nascimento [UNESP]; Modolo, Norma Sueli Pinheiro [UNESP] (My University, 2021)
(1) Background: Intermittent fasting is a nutrition practice in which individuals fast for several hours in a day, mainly with feeding time during the daylight hours. They seek to improve metabolic performance and cellular resistance to stress. In this study, we tested the fasting protocol to investigate the glycemic effect in a laparotomy perioperative period in diabetic rats and histopathologic findings. (2) Methods: The animals were diabetic-induced with alloxan. Two groups were set according to the feeding protocol: free food and intermittent fasting, whose rats could only eat 8 h in the daylight. Both groups were anesthetized, and a laparotomy was performed. We evaluated the glucose levels during the perioperative period, and we accessed organ histology seeking damage of kidney, bowel and liver after surgical trauma, and we evaluated the wound healing process. (3) Results: Glycemic levels were improved in the intermittent fasting group, especially in the post-operative period after laparotomy. Comparing both groups’ tubular damage showed interdependency with mice with worse glycemic level (Z = 2.3; p = 0.0215) and wound-healing parameters showed interdependency with rats with better glycemic status for neovascularization (Z = 2.2; p = 0.0273) and the presence of sebaceous and sweat gland in the healing process (Z = 2.30; p = 0.0215). (4) Conclusions: Intermittent fasting before surgery can be a tool to improve glycemic levels in diabetic rats, with improvement especially in the post-operative period.
Keywords: Diabetes; Intermittent fasting; Perioperative care